Dual-focus versus conventional magnification endoscopy for the diagnosis of superficial squamous neoplasms in the pharynx and esophagus: a randomized trial - Goda, Kenichi; Dobashi, Akira; Yoshimura, Noboru; Aihara, Hiroyuki; Kato, Masayuki; Sumiyama, Kazuki; Toyoizumi, Hirobumi; Kato, Tomohiro; Saijo, Hiroki; Ikegami, Masahiro; Tajiri, Hisao (Endoscopy, 2016)
Background and study aims: Conventional magnification narrow-band imaging (CM-NBI) endoscopy has demonstrated high diagnostic accuracy for superficial squamous neoplasms in the pharynx and esophagus. This study aimed to evaluate the diagnostic utility of the newly developed dual-focus NBI (DF-NBI) compared with that of CM-NBI.Patients and methods: We recruited patients with squamous cell carcinoma (SCC) in the head and neck, or esophagus, or with a history of SCC. The primary endpoint of this prospective controlled non-inferiority trial was the sensitivity of DF-NBI and CM-NBI for detecting superficial carcinoma in the pharynx and esophagus. Secondary endpoints included other diagnostic values and the resolving power of each endoscope. Superficial carcinoma was defined as high grade dysplasia and SCC invading up to the submucosal layer.Results: The study included 93 patients. A total of 28 superficial carcinomas were detected in the pharynx and esophagus. The sensitivities of DF-NBI and CM-NBI for superficial carcinoma were 82 % and 71 %, respectively. The lower limit of the 90 % confidence interval for the difference between the sensitivities exceeded the non-inferiority threshold. The specificity and overall accuracy of DF-NBI vs. CM-NBI were 93 % vs. 90 % and 91 % vs. 86 %, respectively (both non-significant differences). The maximum resolving power of a conventional magnification endoscope was significantly higher than a dual-focus endoscope (7.2 µm vs. 11.6 µm: P < 0.001). Conclusions: The findings indicate the non-inferiority of DF-NBI versus CM-NBI in detecting superficial carcinoma in the pharynx and esophagus. DF-NBI appears to have a resolving power that, although significantly lower, is sufficient to achieve high diagnostic accuracy, comparable to that of CM-NBI.University Hospital Medical Information Network (UMIN, No. 000007585).